Analisis Kelengkapan Penulisan Soap, KIE, dan ICD X pada Rekam Medis di Poli Umum dan KIA-KB Puskesmas X Surabaya - Ayunda Zilul Gosanti; Ernawaty Ernawaty (Universitas Airlangga, 2017)
Based on the standart that Public Health Center “X” completeness of SOAP, KIE, and ICD X must be 100%. The aim of research was to analyze how the completeness of writing SOAP, KIE, and ICD X inGeneral Poly and Health of Mother and Child Family Planning Public Health Center “X”. This study was descriptive research with 500 medical records that consist of 260 for January and 240 for February as sample and they taken by random sampling. The result showed that completeness of SOAP, KIE, and ICD X on January in General Poly were 48% and decrease on February became 45,8%.While Health Mother and Child Family Planning Poly showed that completeness on January were 97,8% and increase on February became 98,6%. The incompleteness of medical records can be influenced by several factors is compliance the health workers who responsible in filling the medical records and they have multi job in Public Health Center “X” also the patient was increase. To minimize the incompleteness of SOAP, KIE, and ICD X, medical staff needs to expose by socialization of medical record to remember their responsibilty of their job description.Keywords : Completeness, medical record, Public Health Center